Mechanical and thermal characterization of multiscale carbon nanotube polypropylene and epoxy composites - Rahmanian, Saeed (2015)
Different types of multiscale fillers were fabricated through growing carbon nanotubes on short fiber and microparticles. The fabricated fillers were incorporated with both thermoplastic and thermoset polymers to evaluate their reinforcing efficiency. First, dense carbon nanotubes (CNTs) were grown uniformly on the surface of short fibers to create multiscale fibers by catalytic chemical vapor deposition. Short fiber reinforced polypropylene composites were fabricated using the multiscale fibers and compared with composites made using neat fibers. Tensile,flexural and impact properties of the composites were measured, which showed evident enhancement of more than 30% in all mechanical properties compared to neat short fiber composites. SEM micrographs of composite fracture surface demonstrated improved adhesion between CNT-coated fiber and the matrix. To evaluate the effect of multiscale fillers on thermoset matrix, CNT and CNT-short carbon fibers (CSCF) were incorporated into an epoxy matrix to fabricate a high performance multiscale composite. The multiscale composites revealed significant improvement of more than 35% in elastic and storage modulus, strength as well as impact resistance in comparison to CNT-epoxy or CSCF-epoxy composites. An optimum content of CNT equal to 0.3 wt.% was found which provided the maximum stiffness and strength. The synergic reinforcing effects of combined fillers were analyzed on the fracture surface of composites through optical and SEM. Another multiscale filler was fabricated through growing CNT on silica microparticles. The CNT-silica fillers were incorporated within polypropylene (PP) as well as epoxy matrix. In spite of the inclusion of multiscale fillers up to 2 wt.%,the reological behaviors of nanocomposites were comparable to the pristine matrix. An improvement by more than 35% was achieved for elastic modulus and tensile strength of nanocomposites, which was discussed by employing micromechanical modeling approaches. The strengthening effects of CNT-silica reinforcement on impact strength of PP or epoxy was revealed by impact tests and was illustrated through fractography of nanocomposites. A micromechanical model was employed to estimate the elastic modulus of multiscale fillers reinforced composites. In this model several effective parameters on the reinforcing role of nanotubes were considered to result in an appropriate estimation.